'You cannot be raped when you are a sex worker’: sexual violence among substance abusing sex workers in Musina, Limpopo province - Anesu, Svinurai; Makhubele, Jabulani Calvin; Ananias, Janetta Agnes; Freeman, Rachel Johanna; Prudence, Mafa; Matlakala, Frans Koketso; Namoonga, Chilwalo Beatrice; Rapholo, Selelo Frank; Ilonga, Hamuse Tiberia Ndanyakuwa; Hasheela, Miriam Winnie (Penerbit Universiti Kebangsaan Malaysia, 2019)
This paper explored the sexual violence experiences of substance abusing sex workers in Musina Border Town of Limpopo Province in South Africa. Substance abuse behaviours is a common phenomenon among sex workers the world over, with this behaviour exposing sex workers to different violations. This paper sought to explore sexual violence among substance abusing sex workers and appraise its potential effect. The study used a qualitative approach and multiple case study design, exploring experiences from ten participants through in-depth interviews. The paper noted that there is high prevalence of sexual assaults amongst substance abusing sex workers. However, these assaults are generally regarded by both the victims and perpetrators as normal, unavoidable occupational hazards of the sex work profession. The sexual violations are perpetrated by clients, potential clients and in some instances, state security agents who are expected to be sanctuaries of protection. The sex work profession is so delicate such that the line between consented sex and sexual assault is easily crossed, and this breach of contract is regarded normal phenomenon in this line of work. Substances are sometimes regarded by clients as payment of sexual services, which creates conflict as sex workers regard substances as facilitators of the sexual relationship. Additionally, sex workers report that they are constantly sexually violated by state security agents like the South African Police Officers, members of the defence forces, home affairs officials who arrests them and later demand for sex in exchange of their freedom. As a marginalized and criminalized group, sex workers’ ordeals are further compounded by their inability to seek protection from the country’s justice system.